Enhanced Anaerobic Biodegradation of Benzoate Under Sulfate-Reducing Conditions With Conductive Iron-Oxides in Sediment of Pearl River Estuary - Zhuang, Li; Tang, Ziyang; Ma, Jinlian; Yu, Zhen; Wang, Yueqiang; Tang, Jia (Frontiers in Microbiology, 2019)
Anaerobic biodegradation of aromatic compounds under sulfate-reducing conditions is important to marine sediments. Sulfate respiration by a single bacterial strain and syntrophic metabolism a syntrophic bacterial consortium are primary strategies for sulfate-dependent biodegradation of aromatic compounds. The objective of this study was to investigate the potential of conductive iron oxides to facilitate the degradation of aromatic compounds under sulfate-reducing conditions in marine sediments, using benzoate as a model aromatic compound. Here, in anaerobic incubations of sediments from the Pearl River Estuary, the addition of hematite or magnetite (20 mM as Fe atom) enhanced the rates of sulfate-dependent benzoate degradation by 81.8% and 91.5%, respectively, compared with control incubations without iron oxides. Further experiments demonstrated that the rate of sulfate-dependent benzoate degradation accelerated with increased magnetite concentration (5, 10 and 20 mM). The detection of acetate as an intermediate product implied syntrophic benzoate degradation pathway, which was also supported by the abundance of putative acetate- or/and H2-utilizing sulfate reducers from microbial community analysis. Microbial reduction of iron oxides under sulfate-reducing conditions only accounted for 2-11% of electrons produced by benzoate oxidation, thus the stimulatory effect of conductive iron oxides on sulfate-dependent benzoate degradation was not mainly due to an increased pool of terminal electron acceptors. The enhanced rates of syntrophic benzoate degradation by the presence of conductive iron oxides probably resulted from the establishment of a direct interspecies electron transfer (DIET) between syntrophic partners. In the presence of magnetite, Bacteroidetes and Desulfobulbaceae with potential function of extracellular electron transfer might be involved in syntrophic benzoate degradation. Results from this study will contribute to the development of new strategies for in situ bioremediation of anaerobic sediments contaminated with aromatic compounds, and provide a new perspective for the natural attenuation of aromatic compounds in iron-rich marine sediments.